Oxidative stress related DNA adducts in the liver of female rats fed with sunflower-, rapeseed-, olive- or coconut oil supplemented diets - Eder, Elisabeth Christiane; Wacker, M.; Lutz, U.; Nair, Jagadeesan; Fang, X.; Bartsch, Helmut; Beland, F. A.; Schlatter, J.; Lutz, W. K. (Chemico-biological interactions, 2006)
Both animal and epidemiological studies support an effect of fatty acid composition in the diet on cancer development, in particular on colon cancer. We investigated the modulating effect of supplementation of the diet of female F344 rats with sunflower-, rapeseed-, olive-, or coconut oil on the formation of the promutagenic, exocyclic DNA adducts in the liver, an organ where major metabolism of fatty acids takes place. 1,N6-ethenodeoxyadenosine (etheno-dA), 3,N4-ethenodeoxycytidine (etheno-dC) and 1,N2-propandodeoxyguanosine from 4-hydroxy-2-nonenal (HNE-dGp) were determined as markers for DNA-damage derived from lipid peroxidation products and markers for oxidative stress. 8-Oxo-deoxyguanosine (8-Oxo-dG) was also measured as direct oxidative stress marker. The body weight of the rats was not influenced by the four diets containing the different vegetable oils during the 4-week feeding period. Highest adduct levels of etheno-dC (430±181 adducts/109 parent bases), HNE-dGp (617±96 adducts/109 parent bases) and 8-Oxo-dG (37,400±12,200 adducts/109 parent bases) were seen in rats on sunflower oil diet (highest linoleic acid content). Highest adducts levels of etheno-dA (133±113 adducts/109 parent bases) were found in coconut oil diet (lowest content of linoleic acid). Weakly positive correlations between linoleic acid content in the four diet groups were only observed for levels of HNE-dGp and 8-Oxo-dG. Neither the diet based on olive oil (which contains mainly oleic acid) nor the diet based on rapeseed oil (containing α-linolenic acid) exerted any significant protective effect against oxidative DNA damage. Our results indicate that a high linoleic acid diet may contribute to oxidative stress in the liver of female rats leading to a marginal increase in oxidative DNA-damage.
Available online 27 october 2005
Gesehen am 23.11.2020